Comparison of stereotactic body radiation therapy with hepatic resection and radiofrequency ablation as initial treatment in patients with early-stage hepatocellular carcinoma - Yang, Zi-liang; Sun, Xu-qi; Tang, Yu-hao; Xiong, Pei-yao; Xu, Li (Frontiers in Oncology, 2022)
Background Stereotactic body radiation therapy (SBRT) has emerged as a novel intervention for early-stage hepatocellular carcinoma (HCC). The outcomes of SBRT, liver resection (LR), and radiofrequency ablation (RFA) as the initial treatment for AJCC stage I HCC patients remain unclear. Methods Patients with AJCC stage I HCC from the Surveillance, Epidemiology and End Results database were analyzed for survival rates using the Kaplan–Meier method and stratified according to tumor size: S subgroup (≤2 cm), M subgroup (>2–3 cm), and L subgroup (>3 cm). For factors including age, year of diagnosis, sex, race, grade, tumor size, AFP, and fibrosis score, propensity score matching was performed to eliminate the imbalance of baseline features and selection bias during groups. Results A total of 4,002 patients were included; the difference in median overall survival (mOS) between the SBRT group and the LR or RFA group in the S subgroup was statistically insignificant (p=0.109 and p=0.744), while that of the RFA group was significantly worse than that of the LR group (p <0.001). In the M and L subgroups, the mOS of the SBRT group was worse than that of the RFA group (p=0.040 and p<0.001, respectively). The mOS of LR was the best when compared with either the SBRT or RFA group regardless of the subgroup M or L (all p<0.001). Conclusion For HCC ≤ 2 cm, SBRT can be used as an alternative treatment for RFA. For patients with HCC larger than 2 cm, RFA can provide better long-term survival than SBRT, while LR remains the best choice.